The use of Collatamp EG in total hip arthroplasty - Logroscino, G.; Malerba, G.; Pagano, E.; Ziranu, A. (Acta Biomedica Atenei Parmensis, 2011)
Total Hip Arthroplasty (THA) is one of the most common orthopedic operations in the world. The number of THA is expected to grow and with it the number of associated complications. Although improved surgical technique and the development of more scrupulous asepsis has decreased the incidence of periprosthetic joint infection (PJI), it remains one of the most feared complications of joint arthroplasty. The purpose of this study is to present the use of antibiotic-loaded collagen sponges (Collatamp® EG) in the prophylaxis and treatment of PJI. For this scope a case report is described. The advantages offered by the antibiotic loaded sponges in terms of high and sustained concentration of antibiotic at the site of infection, diffused by the fully reabsorbable carrier, showed to be a an important adjuvant therapy in the treatment of PJI. Low systemic concentration of the drug and a wide versatility in surgical application are other advantages of this dispositive.